2016
DOI: 10.1097/qai.0000000000000871
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research

Abstract: The Navigation Program is a health department-community agency collaboration to reengage lost HIV clinic patients in Los Angeles County using best practices from disease investigator services locator activities and the Antiretroviral Treatment Access Study (ARTAS), a CDC-recommended intervention. Clinic databases were reviewed to identify HIV patients who: (1) had no HIV care visits in 6-12 months and last viral load was greater than 200 copies per milliliter; (2) had no HIV care visits in >12 months; (3) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Target populations were primarily PWH who had challenges being engaged in HIV care. Examples include PWH with a history of incarceration (n=8) [11, 14-17, 19-21], with recent/new HIV diagnosis (n=5) [10, 14, 18, 20-21], with comorbid conditions such as substance use and mental health problems (n=4) [10, 13, 19, 22], and those who were veterans (n=1) [23], women (n=1) [8], or racial minorities (n=1) [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Target populations were primarily PWH who had challenges being engaged in HIV care. Examples include PWH with a history of incarceration (n=8) [11, 14-17, 19-21], with recent/new HIV diagnosis (n=5) [10, 14, 18, 20-21], with comorbid conditions such as substance use and mental health problems (n=4) [10, 13, 19, 22], and those who were veterans (n=1) [23], women (n=1) [8], or racial minorities (n=1) [10].…”
Section: Resultsmentioning
confidence: 99%
“…Patient navigators engaged in a range of activities that can be summarized with the categorization used in Bradford et al, 2007 [5], i.e., accompanying HIV-positive clients to appointments, coordinating their clients’ appointments, providing non-clinical services (e.g., transportation, food, clothing), providing HIV information, referring clients to HIV care or other health services, and relationship building. Five studies [10-12, 15, 20] indicated that the navigators were “peers” (e.g., being PWH and/or having similar sociodemographic characteristics as the clients), 3 studies [8, 19, 23] indicated that the navigators had professional degrees such as nursing or clinical social work, and 3 studies [5, 14, 16] indicated that the navigators had Bachelors’ degrees. In some studies there was no clear boundary between the roles of patient navigators and case managers (e.g., case management was part of the navigator’s duty or the case manager performed patient navigation [11, 13-14, 16-18]), while others had a clear separation of roles between them or reflected the idea that patient navigation and case management are two separate strategies [5, 9-10, 12, 15, 20, 24-25] (Data not shown in the table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, most HIV navigation program data have not been systematically analyzed, and there is marked heterogeneity in outcome reporting [ 22 ]. Prior evaluations of navigation efforts using public health surveillance data included NIC PWH with similar or higher pre-enrollment viral suppression than our cohort (17% in Seattle [ 28 ], 32% in New York City [ 29 ], 43% in Massachusetts [ 18 ], and 51% in Los Angeles County [ 30 ]). A unique aspect of our program is that some LINCS navigators were placed within public HIV clinics and built trust with clinical teams while also conducting field outreach and utilizing multiple data systems to locate patients.…”
Section: Discussionmentioning
confidence: 99%